Anti-oxidative and cytotoxic attributes of phenolic rich ethanol extract of Musa balbisiana Colla inflorescence - Vageesh Revadigar, Majed Ahmed Al-Mansoub, Muhammad Asif, Mohammad Razak Hamdan, Amin Malik Shah Abdul Majid, Mohd Zaini Asmawi, Vikneswaran Murugaiyah (Journal of Applied Pharmaceutical Science, 2017)
Inflorescence of Musa species is one of the most commonly consumed vegetables in Southeast Asian region. In the present study, chemical composition and antioxidant potential of the ethanolic extract of inflorescence of Musa balbisiana Colla (MbCi) were evaluated. In addition, the extract was also subjected to cytotoxicity testing on a panel of human cancer cell lines. The ethanolic extract of inflorescence of Musa balbisiana Colla was evaluated for antioxidant activity using 1,1-diphenyl-2-picryl-hydrazyl assay (DPPH), 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) and ferric reducing antioxidant power (FRAP) assays. The extract was chemically characterized for total phenolic (TPC) and total flavonoid (TFC) contents and by gas chromatography–mass spectrometry (GC-MS) analysis. Cytotoxicity was evaluated by MTT cell viability assay. The extract showed moderate antioxidant activity in all the antioxidant assays. Chemically, the extract was found to possess high total phenolic (92.01 ± 0.40 μg gallic acid equivalent/mg extract) but low flavonoid (4.852 ± 0.04 μg quercetin equiv./mg extract) contents. In cell viability assay, MbCi extract showed selective cytotoxicity towards HT-29 cell line. Morphological observations show that MbCi has apoptosis inducing nature. GC-MS analysis has revealed the presence of 22 compounds, mainly belonging to steroids, fatty acids and long chain aliphatic compounds, which in part may be responsible for observed antioxidant and cytotoxic activities of ethanol extract. Our study revealed that MbCi has chemotherapeutic potential activity that warrants further investigation.
Keywords: Musa balbisiana Colla,antioxidant,cytotoxicity,morphological changes,apoptosis.